MANAJEMEN SDM PADA BAGIAN LAYANAN PENGADAAN KABUPATEN BLITAR (Ditinjau dari Aspek Manajemen Sumber Daya Manusia) - Tabah Soniawan; M. Naim Musafik (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
In Tesis the title of “MANAJEMEN SDM PADA BAGIAN LAYANAN PENGADAAN KABUPATEN BLITAR”. The purpose is give information about strategy in the devolopment (SDM ASN), ASN organisasion, direct or work execution and controling or evaloation of “BAGIAN LAYANAN PENGADAAN KAB BLITAR” so can give as criticism and balance for instation in the decision about working grow district govemment, The analysis result ratio strategi pengembangan SDM dan pemgembangan pelayanan pada Bagian Layanan Pengadaan Kanbupaten Blitar the ilustration working of district gaverinment Blitar regency is very good.Can see from analisis result of grawing SDM ratio, and service graw the es pecially autonomy ratio, effective ratio, efficient ratio, can see from year to year The suggestion can submit in the Tesis is increasa working sys,tem and good on line access, maximizing trained staff in the proses of managing procurement so as to minimize errors in the procurenent of service goods.